FINGER PAINTING ON THE ADAPTIVE DEVELOPMENT OF FINE MOTOR SKILLS IN PRESCHOOL CHILDREN - Novita Sari; Fitria Hikmatul Ulya; Ninik Ardita Widiarti; Rose Nur Hudhariani (Universitas Karya Husada Semarang, 2026)
Preschool children experience the greatest developmental growth compared to later age groups. In Indonesia, approximately 14,228,917 children are in the developmental age range, and around 10% experience delays in motor development. Preliminary observations found that many preschool-aged children were not yet able to control pencils/crayons properly and were unable to draw straight lines, although these skills should have been achieved according to developmental milestones. To prevent developmental problems, particularly in fine motor skills, finger painting can be introduced as an innovative stimulation method. This study aimed to analyze the effect of finger painting on the adaptive fine motor development of preschool children aged 5–6 years at Al-Azam Kindergarten, Tembalang District. A quasi-experimental design using a one-group pretest–posttest approach.Eighteen children were selected using purposive sampling based on the inclusion criteria.The sample size represented the accessible population that met the study criteria at the research site. The intervention was conducted for two weeks in six sessions. Child development was assessed using a developmental screening instrument.The mean fine motor score increased from 7.94 to 9.06 with a p-value of 0.001. The findings indicate that finger painting improved fine motor development by stimulating children's interest, enthusiasm, imagination, creativity, understanding of shapes and colors, and engagement in artistic activities. Finger painting improved children's creativity, interest, and hand movement coordination. It can be concluded that finger painting significantly influences the adaptive fine motor development of preschool children aged 5–6 years.